Progression of axial spondyloarthritis - Sh. F. Erdes; T. V. Korotaeva (Современная ревматология)
The spectrum of bone lesions in axial spondyloarthritis is of great interest. With inflammation and mechanical influence concurrence in the background, both tissue gain and tissue loss in a particular bone area can occur simultaneously. Moreover, if vertebral bone mass loss, perhaps, can be easily explained by chronic systemic inflammation, the reason of its gain, observed in axial spondyloarthritis remains a mystery. It is unclear whether it is a consequence of enhanced recovery processes after injury, adaptation to altered mechanical stress, response to inflammatory cells activation or cytokines, produced by them, or changes in Wnt signaling pathways (for example). Whether these factors act individually or collectively is also unclear.